2000
DOI: 10.1007/bf02976458
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction events elicited by natural products: Role of MAPK and caspase pathways in homeostatic response and induction of apoptosis

Abstract: Many natural products elicit diverse pharmacological effects. Using two classes of potential chemopreventive compounds, the phenolic compounds and the isothiocyanates, we review the potential utility of two signaling events, the mitogen-activated protein kinases (MAPKs) and the ICE/Ced-3 proteases (caspases) stimulated by these agents in mammalian cell lines. Studies with phenolic antioxidants (BHA, tBHQ), and natural products (flavonoids; EGCG, ECG, and isothiocyanates; PEITC, sulforaphane), provided importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
133
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(141 citation statements)
references
References 123 publications
3
133
0
5
Order By: Relevance
“…104,105 It has been suggested that flavonoids and their metabolites may interact selectively with the MAPK signaling pathways. 102,106 The action of flavonoids on the ERK pathway 83,99,107−110 appears to be mediated by interactions with MAPK kinases MEK1 and MEK2 and potentially membrane receptors. 102,111,112 In fact, flavonoids have close structural homology to specific pharmacological modulators of ERK signaling such as PD98059 (2′-amino-3′-methoxyflavone).…”
Section: ■ Flavonoids and Their Interaction With Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…104,105 It has been suggested that flavonoids and their metabolites may interact selectively with the MAPK signaling pathways. 102,106 The action of flavonoids on the ERK pathway 83,99,107−110 appears to be mediated by interactions with MAPK kinases MEK1 and MEK2 and potentially membrane receptors. 102,111,112 In fact, flavonoids have close structural homology to specific pharmacological modulators of ERK signaling such as PD98059 (2′-amino-3′-methoxyflavone).…”
Section: ■ Flavonoids and Their Interaction With Signaling Pathwaysmentioning
confidence: 99%
“…102,106 The action of flavonoids on the ERK pathway 83,99,107−110 appears to be mediated by interactions with MAPK kinases MEK1 and MEK2 and potentially membrane receptors. 102,111,112 In fact, flavonoids have close structural homology to specific pharmacological modulators of ERK signaling such as PD98059 (2′-amino-3′-methoxyflavone). Moreover, activation of ERK can result in downstream activation of cAMP response element binding protein (CREB), which may lead to changes in synaptic plasticity and memory 113,114 and to upregulation of neuroprotective pathways.…”
Section: ■ Flavonoids and Their Interaction With Signaling Pathwaysmentioning
confidence: 99%
“…For example, accumulating evidence suggests that flavonoids can interact selectively within MAPK signaling cascades in non-neuronal models [104,107]. This could have important implications with regard to their possible sites of action in neurons since members of the MAPK family are involved in signaling to neuronal survival, regeneration, and death [48,136,226].…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%
“…It has been shown by several groups that the activation of these kinases by PEITC correlates with activation of the caspase‐dependent apoptotic pathway, and that chemical inhibition of these kinases blocks this process. For example, chemical inhibition of only JNK activity, and not p38 MAPK or ERK1/2, in human colon adenocarcinoma cells (HT‐29) reduced PEITC‐induced apoptosis 79a. Inhibition of the p38 MAPK with the inhibitor SB202190 did not prevent apoptosis activation by PEITC in PC3 cells; however, treatment with the ERK1/2 inhibitor, PD98059 achieved this effect 82.…”
Section: At High Concentrations Peitc Is Cytotoxicmentioning
confidence: 99%
“…Additionally, PEITC induces extrinsic and intrinsic apoptotic pathways in cancer cells77 by promoting ROS production,77, 78 activating the MAPKs pathways,79 downregulating the anti‐apoptotic proteins Bcl‐2 and Bcl‐x,80 and activating the pro‐apoptotic proteins Bax and Bak 81. Exposure to PEITC causes the activation of stress‐activated MAPKs such as c‐Jun N‐terminal kinase (JNK),77a p38 MAPKs,56, 82 and extracellular signal‐regulated kinase1/2 (ERK1/2) 83.…”
Section: At High Concentrations Peitc Is Cytotoxicmentioning
confidence: 99%